Redefining Pain and Addiction: Creation of a Statewide Curriculum. (November 2020) - Villarroel, Lisa; Mardian, Aram S.; Christ, Cara; Rehman, Shakaib
Objectives: In response to a declared statewide public health emergency due to opioid-related overdose deaths, the Arizona Department of Health Services guided the creation of a modern, statewide, evidence-based curriculum on pain and addiction that would be relevant for all health care provider types. Methods: The Arizona Department of Health Services convened and facilitated 4 meetings during 4 months with a workgroup comprising the deans and curriculum representatives of all 18 medical, osteopathic, physician assistant, nurse practitioner, dental, podiatry, and naturopathic programs in Arizona. During this collaborative and iterative process, the workgroup reviewed existing curricula, established a philosophical framework, and developed a flexible and practical structure for a curriculum that would suit the needs of all program types. Results: The Arizona Pain and Addiction Curriculum was finalized in June 2018. The curriculum aims to redefine pain and addiction as multidimensional public health issues and is structured as 10 core components, each supported by a detailed set of evidence-based objectives. The curriculum includes a set of annual metrics to collect from both programs (focused on implementation progress and barriers) and learners (focused on knowledge, attitudes, and practice plans). Conclusions: To our knowledge, this is the first example of a statewide collaboration among diverse health professional education programs to create a single, standard curriculum. This collaborative process and the nonproprietary Arizona Pain and Addiction Curriculum may serve as a useful template for other states to enhance pain and addiction education.